Regulation and function of sucrose 6-phosphate hydrolase in Streptococcus mutans. - St Martin, E J (1979)
Sucrose catabolism by Streptococcus mutans is initiated by a phosphoenolpyruvate-dependent sucrose phosphotransferase reaction that produces sucrose 6-phosphate the latter is then cleaved by a sucrose 6-phosphate hydrolase reaction that yields glucose 6-phosphate and fructose. We have examined the regulation of the sucrose 6-phosphate hydrolase and found that it was synthesized constitutively whereas sucrose phosphotransferase activity was inducible. However, the levels of both sucrose phosphotransferase and sucrose 6-phosphate hydrolase were repressed when fructose was used as a growth substrate. The specific activity of sucrose 6-phosphate hydrolase in permeabilized cells was approximately 30 mmol/min per mg (dry weight of cells), and it had an apparent Km for sucrose 6-phosphate of 0.3 mM. analysis of a mutant that was missing sucrose 6-phosphate hydrolase activity revealed that its ability to hydrolyze sucrose was reduced.